Is Sentinel Lymph Node Biopsy Necessary in Patients Undergoing Prophylactic Mastectomy? A Systematic Review and Meta‐Analysis. Issue 2 (8th January 2016) - Nagaraja, Vinayak; Edirimanne, Senarath; Eslick, Guy D.
Abstract: The gain by performing sentinel lymph node biopsy (SLNB) during prophylactic mastectomy (PM) is debatable, and we performed a meta‐analysis of existing literature to evaluate that the role of SLNB in subjects undergoing PM. A systematic search was conducted using MEDLINE, PubMed, EMBASE, Current Contents Connect, Cochrane library, Google Scholar, Science Direct, and Web of Science. The search identified 11 relevant articles reporting on patients who underwent SLNB at the time of PM. Data were abstracted from each study and used to calculate a pooled odds ratio (OR) and 95% confidence interval (95% CI). We included 14 studies comprising of 2, 708 prophylactic mastectomies. Among 2, 708 prophylactic mastectomies, the frequency of occult invasive cancer (51 cases) was 1.8% and the rate of positive SLNs (33 cases) was 1.2%. In 25 invasive cancers at the time of PM were found to have negative SLNs which avoided axillary lymph node dissection (ALND). In seven cases with positive SLNBs were found not to have invasive cancer at the time of PM and needed a subsequent ALND. Most of the patients with positive SLNs had locally advanced disease in the contralateral breast. SLNB may be suitable for patients with ipsilateral, locally advanced breast cancer and is not recommend for all patients undergoing PM.